The Australian Work Exposures Study: Occupational Exposure to Polycyclic Aromatic Hydrocarbons - Driscoll, T.; Carey, Renee; Peters, S.; Glass, D.; Benke, G.; Reid, Alison; Fritschi, Lin (2015)
INTRODUCTION: The aims of this study were to produce a population-based estimate of the prevalence of work-related exposure to polycyclic aromatic hydrocarbons (PAHs), to identify the main circumstances of exposure and to describe the use of workplace control measures designed to decrease those exposures. METHODS: The analysis used data from the Australian Workplace Exposures Study, a nationwide telephone survey which investigated the current prevalence and exposure circumstances of work-related exposure to 38 known or suspected carcinogens, including PAHs, among Australian workers aged 18-65 years. Using the web-based tool OccIDEAS, semi-quantitative information was collected about exposures in the current job held by the respondent. Questions were addressed primarily at tasks undertaken rather than about self-reported exposures. RESULTS: Of the 4,993 included respondents, 297 (5.9%) were identified as probably being exposed to PAHs in their current job [extrapolated to 6.7% of the Australian working population-677 000 (95% confidence interval 605 000-757 000) workers]. Most (81%) were male; about one-third were farmers and about one-quarter worked in technical and trades occupations. In the agriculture industry about half the workers were probably exposed to PAHs. The main exposure circumstances were exposure to smoke through burning, fighting fires or through maintaining mowers or other equipment; cleaning up ash after a fire; health workers exposed to diathermy smoke; cooking; and welding surfaces with a coating. Where information on control measures was available, their use was inconsistent. CONCLUSION: Workers are exposed to PAHs in many different occupational circumstances. Information on the exposure circumstances can be used to support decisions on appropriate priorities for intervention and control of occupational exposure to PAHs, and estimates of burden of cancer arising from occupational exposure to PAHs.